Resin infiltration technique and fluoride varnish on white spot lesions in children: Preliminary findings of a randomized clinical trial - KALYONCU, IŞIL ÖZGÜL (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2018)
Aim: To clinically assess the efficacy of resin infiltration versus fluoride varnish for arresting white spot lesions (WSLs) on permanent teeth in children. Subjects and Methods: Among the children referred to the our University, Faculty of Dentistry, Department of Pediatric Dentistry, 23 aged between 8u14 with 81 anterior WSLs were included in the study. The participants were randomly assigned to either the resin infiltration group or the fluoride varnish group. WSLs were assessed using a laser fluorescence device (DIAGNOdent pen, Kavo, Germany) and were characterized at baseline, immediately following resin infiltration application and at a 6-month follow-up. For the statistical analyses, the IBM SPSS Statistics 22 (IBM SPSS, Turkey) program was used to assess the findings of the study. Results: Participant retention was 100% at 6 months. There was no significant difference between the two groups when baseline DIAGNOdent (DD) values were compared (P 0.05). The reduction in 6-month follow-up DD values were statistically significant in both groups relative to baseline values. The 6-month values of the resin infiltration group were statistically lower than those of the fluoride varnish group (P = 0.028, P < 0.05). Conclusions: Resin infiltration and fluoride varnish are clinically feasible and efficacious methods for the treatment of anterior WSLs. The inhibition of caries progression by resin infiltration should now be considered an alternative to fluoride treatment.
Keywords: Children; fluoride varnish; resin infiltration technique; white spot lesions; CARIES LESIONS; ENAMEL LESIONS; PROGRESSION